About the so-called «Bug series» of the Middle Bug region (Ukrainian Shield). Article 3. Problems of origin and age. - Kyrylyuk, V.P. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2023)
The name «Bug Series» was introduced into the Precambrian stratigraphic scheme of the Ukrainian Shield more than half a century ago. During this period, ideas about the composition and age of the series changed several times, but at the same time, until recently, the opinion of various studies about its stratigenic nature remained unchanged. In recent years, a number of publications have appeared in which other views on the origin of the «Bug series» are expressed. Initially, they concerned only individual petrographic groups, such as carbonate and magnetite-bearing rocks, which were attributed to endogenous (magmatic) origin. Later, an opinion was expressed about the nonstratigenic origin of the entire «Bug Series», and some authors propose to abandon the dismemberment of the Early Precambrian granulite complexes into suites altogether. These ideas are based only on the materials of the study of local objects obtained by drilling and geophysical methods, and they do not take into account the results of regional geological and stratigraphic studies. Simultaneously with new ideas about the genesis of the «Bug series», an attempt is being made to link its origin with faults and to revise its age. In order to discuss the problem of the «Bug series», a series of publications has been prepared, in which the main generalized data of many years of regional geological and thematic studies on the composition, structure, stratigraphic and structural position of the units belonging to the «Bug series» are presented. The cycle consists of three separate articles. The first article [Kyrylyuk, 2022a] characterizes the composition of subdivisions and rock associations included in the «Bug series» in the current Precambrian stratigraphic scheme of the Ukrainian Shield. In the second article of the series [Kyrylyuk, 2022б], the ideas about the structural position of the «Bug series» and its subdivisions are considered. This final article is devoted to consideration of ideas about the primary nature of the «Bug series» and its age. As for the Kosharo-Aleksandrovskaya and Khashchevo-Zavalyevskaya suites, the composition, structure, and structural-stratigraphic position of these suits in the stratotype region unambiguously testify to their original stratigenic nature. The problem is only the origin of the rock association of magnetic anomalies, which are erroneously included in the Khashchevo-Zavalievskaya suite. But this association, according to the sum of the signs that are given in the article, also has the most probable lithogenic origin. All subdivisions of the «Bug series» are part of the unified Pobug granulite-gneiss complex of the Lower Archean. Its «stratigraphic age» is not younger than 3.8 Ga, and all younger dates indicate a long-term granulite metamorphism of the complex up to 2.0—1.9 Ga.